Demographic stagnation and decline in Spain: A cause for concern? - Serrano-Martínez José-María; García-Marín Ramón (Bulletin of Geography. Socio-Economic Series, 2018)
For years, the Spanish population has been rapidly ageing, showing signs of atony and stagnation. Between 1996 and 2007, in a phase of economic growth, the entry of foreign immigrants drove a global increase in population. But after the economic recession migratory flows show negative net balances. Our objective is to explain and confirm the demographic regression suffered by Spain. We are also interested in showing how the recent and intense immigration process has failed to generate significant changes in natural demographic characteristics and trends. National censuses, published by the National Institute of Statistics (INE), are our main source of demographic data. The analysis of the most recent relevant scientific literature has allowed us to compare opinions and discuss results. The data confirm an uncertain and worrying future for the Spanish population.